A community led innovation benefiting women and children: Health facilities and credit cooperative work together to promote maternal health care in Sahare VDC, Nepal. Issue 9 (2nd September 2018) - Flueckiger, Rebecca M.; Colaco, Rajeev; Adhikari, Bibek; Palas, Joshi; Kandel, Ghanshyam; Kish Doto, Julia; Lama, Shova; Timmons, Robert; Adhikari, Damodar
Abstract: Monetary incentives effectively promote antenatal care (ANC) attendance. However, in Nepal, late release of incentives is common, which leads to delays in payment to mothers, thereby negating the intended motivation. We evaluate a novel innovation where community organizers partnered with a Women's Saving and Credit Cooperative to provide interest-free loans for timely distribution to mothers. Through focus group discussions and interviews we found that monetary incentives motivate women to seek ANC services and timely incentives provide critical commodities postpartum. This qualitative evaluation shows the importance of timeliness in delivery of incentives and demonstrates the success of a community partnership innovation.